2002
DOI: 10.1093/humupd/8.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms and single nucleotide polymorphisms of the FSH receptor gene: implications for human reproduction

Abstract: The FSH receptor shows three single nucleotide polymorphisms (SNPs), one in the promoter and two in exon 10. In addition, the FSH receptor mRNA undergoes extensive alternative splicing. While no physiological role for the SNP in the promoter and for alternative spliced isoforms has been demonstrated so far, the SNPs in exon 10 result in four discrete allelic variants characterized by the amino acid combinations Thr307-Asn680, Ala307-Ser680, Ala307-Asn680 and Thr307-Ser680. Several studies have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
110
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 94 publications
7
110
0
9
Order By: Relevance
“…In the receptor protein, position 307 may be occupied by either Ala or Thr, and position 680 by either Asn or Ser [1,2]. Most available studies were focused on position 680 [3], whereas polymorphism 307 was rarely considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the receptor protein, position 307 may be occupied by either Ala or Thr, and position 680 by either Asn or Ser [1,2]. Most available studies were focused on position 680 [3], whereas polymorphism 307 was rarely considered.…”
Section: Discussionmentioning
confidence: 99%
“…Most available studies were focused on position 680 [3], whereas polymorphism 307 was rarely considered. Position 307 codifies for an amino-acid located within the extracellular domain in the FSHbinding region of the protein [1]: it can affect the hormone-binding ability of the receptor and is crucial for FSH-mediated signal transduction events [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, genetic studies focus on genes or gene products (molecular biomarkers) that might serve in the assessment of patient's fertility treatment prognosis in order to personalize the treatment accordingly. These studies rely on the identification and characterization of natural variants or polymorphisms in DNA sequence among individuals [23,35].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that differences seen between individuals or subpopulations of patients are often due to genetic variations, known as single nucleotide polymorphisms (SNPs) in coding regions responsible for the synthesis of hormone receptors, metabolic enzymes or transport molecules, which are specific targets for pharmaceutical drugs. The most studied SNP associated with ovarian response to COS, is the follicle stimulation hormone receptor (FSHR) variant (Ans 680 Ser), which along with estrogen receptor alpha variant (ESR1 gene, Pvull T/C) are practically the only genetic markers applied in clinical tests [4][5][6][7].…”
mentioning
confidence: 99%